Low-fat versus Low-carbohydrate Diet - Dalal J. Alsharif (Journal of Nature and Science of Medicine)
The global obesity rate has risen significantly, prompting research into the optimal dietary strategies for weight loss, particularly in relation to macronutrient composition. Despite numerous studies, the most effective macronutrient balance for weight reduction remains under debate. The objective of this article is to compare the impacts of a low-carbohydrate diet and a low-fat diet on weight loss and cardiovascular health. A comprehensive literature review was conducted across PubMed, Scopus, Web of Science, and Google Scholar. Studies included randomized controlled trials and systematic reviews to provide a broad analysis of the evidence on a low-carbohydrate versus a low-fat diet. Short-term weight loss was significantly higher with a low-carbohydrate diet compared to an unrestricted low-fat diet. However, when matched for calorie intake, no significant difference in weight was observed between the two diets, suggesting that total calorie intake may be more influential than macronutrient composition. Notably, a low-carbohydrate diet induced a greater decrease in triglyceride levels and an increase in both high-density lipoprotein and low-density lipoprotein cholesterol levels compared to a low-fat diet.